Ethnic Identity Types of Russian Youth as an Indicator of a Positive Readiness to Accept the Forced Migrants from Ukraine - Анастасия Васильевна Гришина; Сергей Леонидович Лунин (Rossijskij psihologičeskij žurnal., 2015)
This article describes the currently conducted research of ethnic identity types and ethnic stereotypes of Russian youth and their inSuence on relations with the forced migrants from Ukraine. The introductory part of the paper is devoted to the relevance of the study, including a brief description of changes in the migration situation in Russia in 2014. The main part of the article reveals the concept of ethnic identity and ethnic stereotypes, which are described in the context of inter-ethnic relations. The following is a classiTcation of types of ethnic identity by G.0U.0Soldatova and S.0V.0Ryzhova: hypoidentity, positive ethnic identity and hyperidentity. Further discloses the concepts of ethnic image and ethnic stereotype, describes the type of person most likely to mastering and distribution of ethnic prejudices and the formation of ethnic stereotypes. The article also gives a review of the main diUculties that displaced persons may face in the process of social and psychological adaptation to the new place of residence. According to the authors, Ukraine immigrants have the basis for successful social and psychological integration, however, the level of social tension in attitude to Ukrainian migrants is growing, ethnic conSicts occur more often. In order to identify the main causes of this contradiction, it was decided to carry out an empirical study of Russian students’ relations to forced migrants from Ukraine. The following is a description of the organizational phase of the study: its goal, hypotheses and objectives, a description of the selected sample and methodological tools for collecting empirical data, and author proTles. As a result of the study it is planned to draw conclusions about the dependence of positive acceptance of forced migrants on the type of ethnic identity and the level of tolerance.